The Sustainable Corporate Strategy in Industrial Goods Markets - Niski, Alfred; Krause, Stefanie; Drusche, Olaf (Ökologisches Wirtschaften - Fachzeitschrift, 2020)
Classical management thinking and traditional manufacturing processes will reach their limits soon. There is a great need for innovative sustainability-orientated business models. Has a market-oriented, sustainability-oriented corporate strategy the potential for successful marketing of industrial goods in a monopolistic market?